(untitled) (Journal of Information Technologies in Education (ITE), 2011)
In the article the problem of modernization of individual studies of students rises by modern facilities of computer-reference educational environment. The criteria of determination of level of ІКТ-компетентності of teachers-предметників which work with a virtual class are given, the model of integration of virtual class is described in an educational-educate process. Research of virtual class is in-process presented as a computer-reference educational environment.